2003
DOI: 10.1177/1066480703252755
|View full text |Cite
|
Sign up to set email alerts
|

Live Supervision: A Review of the Research

Abstract: This article reviews research on live supervision published within the past 12 years. The focus of the research on live supervision can be conceptualized as addressing its prevalence and use, the impact of live supervision interventions, and perceptions of live supervision by supervisors, trainees, and clients. Implications for supervisors, practitioners, and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Clinical supervision can provide a new sense of clarity or a different point of view, while at the same time allowing for the identification of "blind spots," areas unrecognized by the trainee as requiring additional focus (Littrell et al 1979;Weil 2000). The use of live (in the room) supervision is well documented in the literature, and there has been specific attention given to the student and supervisor perspective on this experience (Champe and Kleist 2003). This type of interaction appears to enhance the trainee's skills, contribute to their professional development, increase their confidence and competence, and provide personal support (Hendrickson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical supervision can provide a new sense of clarity or a different point of view, while at the same time allowing for the identification of "blind spots," areas unrecognized by the trainee as requiring additional focus (Littrell et al 1979;Weil 2000). The use of live (in the room) supervision is well documented in the literature, and there has been specific attention given to the student and supervisor perspective on this experience (Champe and Kleist 2003). This type of interaction appears to enhance the trainee's skills, contribute to their professional development, increase their confidence and competence, and provide personal support (Hendrickson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the various techniques available is critical to assessing how they ultimately impact the training of students. Live supervision is the most common supervision technique utilized in training medical professionals and has been in existence for over 50 years (Champe and Kleist 2003). Live supervision is also used to train professionals in clinical settings such as genetic counseling, marriage and family therapy, counseling, social work, psychology, psychiatry, and other specialties in the mental health field (Champe and Kleist 2003).…”
Section: Supervision Techniques In Other Fieldsmentioning
confidence: 99%
“…Live supervision is the most common supervision technique utilized in training medical professionals and has been in existence for over 50 years (Champe and Kleist 2003). Live supervision is also used to train professionals in clinical settings such as genetic counseling, marriage and family therapy, counseling, social work, psychology, psychiatry, and other specialties in the mental health field (Champe and Kleist 2003). Live supervision can be defined in various ways including co-counseling or co-therapy, supervisor present in the session but remains silent, and remote observation (Hendrickson et al 2002;Marini and Stebnicki 2009;Smith 2009).…”
Section: Supervision Techniques In Other Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that greater perceived helpfulness and less perceived intrusiveness of live supervision predicted clients' overall satisfaction with the therapy received. Champe and Kleist (2003) have issued a call for research on the experiences of clients who participate in live supervision. While there is some literature on the experience of trainees receiving live supervision (Mauzey and Erdman, 1997;Moorehouse and Carr, 2001;Wark, 1995;Wong, 1997), few studies exist that have empirically studied the client's experience of therapy with a therapist trainee receiving live supervision (Locke and McCollum, 2001;Piercy et al, 1986).…”
Section: Introductionmentioning
confidence: 99%